Intra-Venous Lidocaine to Relieve Neuropathic Pain: A Systematic Review and Meta-Analysis - Zhu, Bo; Zhou, Xiayun; Zhou, Qinghe; Wang, Haiyan; Wang, Shougen; Luo, Kaitao (Frontiers in Neurology, 2019)
Background: The prevalence of neuropathic pain is estimated to be between 7% and 10% in the general population. The efficacy of intravenous (IV) lidocaine has been studied by numerous clinical trials on patients with neuropathic pain. The aim of this systematic review and meta-analysis was to evaluate the efficacy of IV lidocaine compared with a placebo for neuropathic pain and secondly to assess the safety of its administration. Methods: A literature search on PubMed, Scopus, CENTRAL (Cochrane Central Register of Controlled Trials) and Google scholar databases was performed for relevant studies published up to February 2019. Randomised controlled trials (RCTs) evaluating IV lidocaine treatment for pain relief in patients with neuropathic pain were included. Results: 26 articles met the inclusion criteria. Patients with varied aetiology of neuropathic pain were among the patient samples of these studies. 15 articles were included for quantitative analysis. Lidocaine was superior to a placebo in relieving neuropathic pain in the early post-infusion period (Mean Difference [MD] = -11.9; 95% Confidence interval [CI]: -16.8 to -7; p<0.00001). Multiple infusions of lidocaine over a period of 4 weeks, however, had no significant effect on reliving neuropathic pain (MD = -0.96; 95% CI: -2.02 to 0.11; p=0.08). IV lidocaine was also associated with a significant number of adverse events compared to a placebo (Odds Ratio [OR] = 7.75; 95% CI: 3.18 to 18.92; p<0.00001). Conclusion: Our study indicates that while IV lidocaine is effective in pain control among patients with neuropathic pain in the immediate post-infusion period, it does not have a long-lasting, persistent effect. IV infusions of the drug are associated with an increased risk of side effects compared to a placebo. However, the risk of serious adverse events is negligible. Further, well-designed RCTs evaluating the effects of various dosages and infusion periods of IV lidocaine are required to provide clear guidelines on its clinical use.